Orientation of the Egg at Laying - Is the Pointed or the Blunt End First? - Salamon , Attila; Kent, John P. (International Journal of Poultry Science, 2014)
While the avian egg is formed in the oviduct, it acquires its shell membranes and shape in the isthmus and the calcified shell in the shell gland/uterus. However, in domestic species not all eggs are laid pointed end first, which led to the suggestion that egg rotation can occur in the oviduct prior to laying producing the blunt end first. However, not all studies were in agreement as to which end the pointed or the blunt-comes out first. Here, opportunistic observation of laying behaviour in domestic geese and ducks was carried out. 89.47% of the single yolked (SY) goose eggs were laid pointed end first. Goose age and dimensions did not influence the orientation of the egg, though the 12 blunt end first eggs were heavier and wider. 85.52% of the SY duck eggs were laid pointed end first. However, in double yolked (DY) duck eggs evidence was presented showing that the yolks closer to the airspace (blunt end) tend to be heavier (Salamon and Kent, 2013a) and had higher levels of fertilization (Salamon and Kent, in press) consistent with the yolk at the blunt end of the egg being ovulated first and suggests that the blunt end of these large eggs was caudal in the oviduct during egg formation. Questions remain to be answered.